Personalised System of Instruction in Teaching Mathematics - Vaishnav, Rajshree (International Journal of Advanced Research in Peace, Harmony and Education; Vol 7 No 1 (2022): International Journal of Advanced Research in Peace, Harmony and Education, 2022)
The vast majority of children do not reach their full potential in terms of learning. The purpose of this study is to determine how successful teaching methods are for acquiring subject mastery. The present study was taken up to investigate the effectiveness of personalised system of instruction for teaching mathematics to middle school children. This study was conducted on middle school pupils as the concepts gained at this level will act as foundation and assist them in achieving their further educational goals. A quasi-experimental study was conducted on the middle school students of Nagpur city of Central Board of Secondary Education using pretest-posttest nonequivalent control group design. Each group consisted of 25 participants. One of the group was exposed to traditional teaching method and the other was exposed to personalised system of instruction. The scores were subjected to t test and the results revealed that experimental group performed better than the control group. Thus, the study encourages the use of PSI to improve performance of middle school children in the subject of mathematics. It is suggested that it can be used to gain mastery learning over concepts of mathematics as well as other subjects at the middle school level which can promote high school performance. How to cite this article: Vaishnav R. Personalised System of Instruction in Teaching Mathematics. Int J Adv Res Peace Harm Edu 2022; 7(1): 23-26.